If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -5) + -7 = -4(-3y + 2) + -3y Reorder the terms: 3(-5 + y) + -7 = -4(-3y + 2) + -3y (-5 * 3 + y * 3) + -7 = -4(-3y + 2) + -3y (-15 + 3y) + -7 = -4(-3y + 2) + -3y Reorder the terms: -15 + -7 + 3y = -4(-3y + 2) + -3y Combine like terms: -15 + -7 = -22 -22 + 3y = -4(-3y + 2) + -3y Reorder the terms: -22 + 3y = -4(2 + -3y) + -3y -22 + 3y = (2 * -4 + -3y * -4) + -3y -22 + 3y = (-8 + 12y) + -3y Combine like terms: 12y + -3y = 9y -22 + 3y = -8 + 9y Solving -22 + 3y = -8 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -22 + 3y + -9y = -8 + 9y + -9y Combine like terms: 3y + -9y = -6y -22 + -6y = -8 + 9y + -9y Combine like terms: 9y + -9y = 0 -22 + -6y = -8 + 0 -22 + -6y = -8 Add '22' to each side of the equation. -22 + 22 + -6y = -8 + 22 Combine like terms: -22 + 22 = 0 0 + -6y = -8 + 22 -6y = -8 + 22 Combine like terms: -8 + 22 = 14 -6y = 14 Divide each side by '-6'. y = -2.333333333 Simplifying y = -2.333333333
| 11=v+20 | | -2(3x-5)=46 | | 10+7= | | -7-x=-11+2x | | c+2(c-r)= | | -3a=-7(8+a)+-4 | | 5x-4+2(5x+2)=-3(x+4) | | -6(7+2(-6))=30 | | 2(x+6)=6-4(x+6) | | 5(x-3)-2=18 | | 6(y+2)=5y+18 | | -4+n=7 | | -48-9x=-(-12+4x) | | 3(2y+6)=2(4Y-5) | | (k+1)5= | | -6x-12+16=-44 | | y=-0.026x^2+0.51x | | 48-9x=-(-12+4x) | | 7(2t+1)-10=t-(t+2) | | 8a-3a+a=24 | | 3(6+x)=2 | | A(n)=1+(n-1)(-6) | | 56u^2-122u+42= | | X+11=132 | | A(n)=1-(n-1)(-6) | | 0=-55x+440 | | (x^3-8)=0 | | 7(3x-7)+10x= | | 8y+4-2(-6y-3)=2(y-3) | | nA=-1+1.1(4) | | 0=440-55x | | nA=-1+1.1(2) |